The Impact of Organizational Culture Differences, Synergy Potential, and Autonomy Granted to the Acquired High-Tech Firms on the M&A Performance. Issue 3 (June 2019) - Tarba, Shlomo Y.; Ahammad, Mohammad F.; Junni, Paulina; Stokes, Peter; Morag, Omri
The aim of the article is to examine the factors influencing the overall acquisition performance of the companies acquiring the high-tech firms. The data were gathered during 2007-2009 via a cross-sectional survey using a questionnaire on a sample of Israeli high-tech firms that were engaged in acquisitions. Given its global leading role in the high-tech sector, Israel constitutes an important site for the study of mergers in this industrial domain. The findings indicate that synergy potential (similarities and complementarities) between high-tech merging firms, effectiveness of post-acquisition integration, and organizational cultural differences positively influence the overall acquisition performance merging high-tech firms. Moreover, our findings suggest that organizational cultural differences moderate the relationship between effectiveness of post-acquisition integration and overall acquisition performance as such that positive effect of effectiveness of post-acquisition integration is higher when organizational differences are higher. Our findings indicate that organizational cultural differences also positively moderate the relationship between autonomy granted and the overall acquisition performance. An important contribution of the present article is the development of a conceptual framework incorporating the direct and moderating effect of organizational cultural differences and autonomy granted on the overall performance of acquisition.